Location Decision Making of "Creative" Industries: The Media and Computer Game Sectors in Dublin, Ireland. (7th October 2014) - Murphy, Enda; Fox‐Rogers, Linda; Redmond, Declan
Abstract: There has been significant research undertaken examining the "creative class" thesis within the context of the locational preferences of creative workers. However, relatively little attention has been given to the locational preferences of creative companies within the same context. This paper reports on research conducted to qualitatively analyse the location decision making of companies in two creative sectors: media and computer games. We address the role of the so‐called "hard" and "soft" factors in company location decision making within the context of the creative class thesis, which suggests that company location is primarily determined by "soft" factors rather than "hard" factors. The study focuses upon "core" creative industries in the media and computer game sectors and utilises interview data with company managers and key elite actors in the sector to investigate the foregoing questions. The results show that "hard" factors are of primary importance for the location decision making in the sectors analysed, but that "soft" factors play quite an important role when "hard" factors are satisfactory in more than one competing city‐region.